Omnibus Law sebagai Strategi Mengatasi Disharmonisasi Peraturan di Indonesia - Hastuti S., Tuti Tri; Hoessein, Zainal Arifin (UI Scholars Hub, 2026)
This article discusses the challenges in implementing the Omnibus Law (OL) both as a regulatory system and as a tool for harmonizing regulations within Indonesia’s legal positivist tradition and its complex, non-simple regulatory hierarchy, from the perspectives of legislative consolidation theory, regulatory coherence theory, and multilevel regulation theory. This study is based on the assumption that OL, within the framework of legal positivism (norm hierarchy system), faces problems in applying these three theories. The research employs normative juridical and comparative methods, analyzing national regulations and international research findings. The results indicate, first, that the positioning of OL, which does not yet include implementing regulations, conflicts with the principles of norm hierarchy; second, substantive harmonization requires OL to integrate elements of both legal positivism (civil law) and common law; third, it is suggested that OL be incorporated into Law No. 12/2011 using a reconstruction approach to the regulatory system, where legislative consolidation, regulatory coherence, and multilevel regulation serve as guidelines to strengthen legal harmonization.